2009
DOI: 10.1038/nbt.1563
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of post-translational modulators of transcription factor activity in human B cells

Abstract: The ability of a transcription factor to regulate its targets is modulated by a variety of genetic and epigenetic mechanisms, resulting in highly context-dependent regulatory networks. However, high-throughput methods for the identification of proteins that affect transcription factor activity are still largely unavailable. Here we introduce a systems biology framework, MINDy (Modulator Inference by Network Dynamics), for the genome-wide identification of post-translational modulators of transcription factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
260
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(266 citation statements)
references
References 49 publications
4
260
0
2
Order By: Relevance
“…By analysing the cell cycle activation of NDR1/2 via kinase assays and phosphorylation specific antibodies, Cornils et al (2011) defined human NDR1/2 as cell cycle regulated kinases that are mainly activated upon the G1/S cell cycle transition [76]. They further showed that NDR1/2 are essential for the G1/S cell cycle transition by regulating p21 and c-myc levels [76][77][78]. Significantly, NDR1/2 kinases require only MST3 kinase activity for this cell cycle role, but not MST1/2 [76,79].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 99%
“…By analysing the cell cycle activation of NDR1/2 via kinase assays and phosphorylation specific antibodies, Cornils et al (2011) defined human NDR1/2 as cell cycle regulated kinases that are mainly activated upon the G1/S cell cycle transition [76]. They further showed that NDR1/2 are essential for the G1/S cell cycle transition by regulating p21 and c-myc levels [76][77][78]. Significantly, NDR1/2 kinases require only MST3 kinase activity for this cell cycle role, but not MST1/2 [76,79].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 99%
“…modulators of transcription factor activity and the effect on expression of their target genes (11,(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies rely on knowledge of TF-target interactions to decipher the transcriptional network (27)(28)(29)(30). However, few algorithms are able to identify modulators of TF-target connectivity at a network level (14)(15)(16). These typically derive information from statistical relationships across conditions between the mRNA abundance of gene triplets: the TF of interest, a candidate modulator, and a target of the TF.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Approaches such as Algorithm for the Reconstruction of Accurate Cellular Networks have been developed with this issue in mind, as it can eliminate indirect transcriptional interactions from inferred networks [147]. Furthermore, methods such as Modulator Inference by Network Dynamics can detect three-way interactions between gene products (such as protein kinases), downstream regulators and their targets [148].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%